A Central African Jubilee or fifty years with the Gospel in "The Beloved Strip" - Arnot, F.S. Jubilee Conference 1931; Arnot, Frederick Stanley, 1858-1914 (London, UK Pickering and Inglis, 1931)
Contents : Papers from the F.S. Arnot Jubilee Conference.
The F.S. Arnot Jubilee Conference held to commemorate the Jubilee (50yrs) of Frederick Stanley Arnot's setting out for Africa in 1881
Keywords: Missions -- brethren -- Africa -- Adresses, essays, lectures